Long term risks of stroke, myocardial infarction, and vascular death in "low risk" patients with a non-recent transient ischaemic attack. - Clark, T; Murphy, M; Rothwell, P (2003)
BACKGROUND: Previous studies of prognosis after a transient ischaemic attack (TIA) have recruited patients soon after the event, when the risk of stroke is very high. However, the majority of patients survive for many years after a TIA, and the need for continued preventive treatment to lower vascular risk will need to be reassessed at a later date. OBJECTIVE: To determine the long term risks of stroke and other vascular events in patients with TIA who survive the initial high risk period. METHODS: 290 patients were studied who had initially been followed up after a TIA in the Oxford community stroke project and in a contemporaneous hospital based cohort study, and who were alive and stroke-free at the end of planned follow up in 1988. All patients were followed for a further 10 years, and the risks of major vascular events (stroke, myocardial infarction, vascular death) were determined. Standardised mortality ratios (SMR) were calculated from the observed numbers of fatal events and the number expected on the basis of age and sex in the general population. RESULTS: Median time since last TIA was 3.8 years (interquartile range, 2.2 to 5.8 years). The risk of major vascular events was constant through time. The 10 year risk of first stroke was 18.8% (95% confidence interval (CI), 13.6 to 23.7; 45 events). The 10 year risk of myocardial infarction or death from coronary heart disease was 27.8% (95% CI, 21.8 to 33.3; 67 events) and there was a significant excess of fatal coronary events compared with that expected in the general population (SMR = 1.47; 95% CI, 1.10 to 1.93; p = 0.009). A total of 114 patients had at least one major vascular event, with a 10 year risk of any first stroke, myocardial infarction, or vascular death of 42.8% (95% CI, 36.4 to 48.5). CONCLUSIONS: The overall risk of major vascular events remains high for 10 to 15 years after a TIA. It is important therefore that preventive treatments are continued in the long term, even in apparently "low risk" patients who have already survived free of stroke for several years.